1992
DOI: 10.1093/geronj/47.2.p85
|View full text |Cite
|
Sign up to set email alerts
|

Possible Selves and Perceived Health in Older Adults and College Students

Abstract: Two studies were conducted to assess motivational aspects of the self by measuring hoped-for and feared possible selves among a sample of older adults and college students. It was predicted that health-related possible selves would be predominant among older adults, but not college students, and that self-regulatory aspects of possible selves would be related to perceived health. Data were collected through interviews and questionnaires. Older adults were significantly more likely to have possible selves in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
156
2
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(167 citation statements)
references
References 0 publications
8
156
2
1
Order By: Relevance
“…Researchers have suggested that, in order to maintain well-being, individuals change and reevaluate their possible selves in response to changing life circumstances (Hooker, 1992;Strauss & Goldberg, 1999). Such findings are consistent with participants' emphasis on selfknowledge as a mechanism for personal growth.…”
Section: The Self In Health Behavior Change / Fleury and Sedikidesmentioning
confidence: 55%
See 2 more Smart Citations
“…Researchers have suggested that, in order to maintain well-being, individuals change and reevaluate their possible selves in response to changing life circumstances (Hooker, 1992;Strauss & Goldberg, 1999). Such findings are consistent with participants' emphasis on selfknowledge as a mechanism for personal growth.…”
Section: The Self In Health Behavior Change / Fleury and Sedikidesmentioning
confidence: 55%
“…Understanding these domains is essential, because it is in these domains that individuals will attend to their behavior, generate commitment to behavioral change, and attempt to regulate behavior (Markus, 1983). Older adults have been shown to be significantly more likely to report health-related possible selves than younger adults; regardless of age, those with a hoped-for healthrelated possible self engaged in more healthprotecting behaviors (Fleury et al, 2002;Hooker, 1992;Hooker & Kaus, 1992, 1994.…”
Section: The Self In Health Behavior Change / Fleury and Sedikidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible selves allow individuals to adapt to new roles and circumstances throughout the lifespan. Evidence from the developmental literature shows that there are significant age differences in the domains of possible selves that are salient, their centrality or importance to the individual, how extensive or elaborate they are, and the strength of their link to plans and behavioral strategies (Frazier, 1993;Frazier et al, 2000;Frazier et al, 2002;Hooker, 1992;Hooker & Kaus, 1992;1994;Markus & Nurius, 1986). There are also age differences in the selfregulatory processes associated with possible selves (Hooker & Kaus, 1992;1994;Frazier & Hooker, 2006).…”
Section: Theory and Research On Possible Selvesmentioning
confidence: 99%
“…The most salient domains for hoped-for possible selves are occupation, family, and success. The most salient domains for feared possible selves are family, success, and dependence (Frazier, Montgomery, Barreto, Perez, Hinton, & Jauregui, 2003;Hooker, 1992;Oyserman & Markus, 1990). …”
Section: Theory and Research On Possible Selvesmentioning
confidence: 99%